(untitled) (Journal of the College of Basic Education, 2022)
This paper aims at exploring the dynamics of power in Lillian Hellman’s The Children’s Hour which deals with a typical educational setting. Besides being a ‘site of national citizen building’, and a place where the State authorities ensure the ‘minimum common level of enculturation and socialization,’ the educational settings, the paper argues, offer a unique insight into the social and cultural structure of society. As these settings influence society, and are themselves influenced by it, Hellman’s play reveals as much about the teachers, administrators, as about the students. The play, which takes place in an all-girl private boarding school, tells a lot about American society in the 1930s. Hellman’s main focus is not to give solutions to the problems and questions raised, rather, she aspires to draw attention to them and raise public awareness about the dangers of neglecting them. The paper discussion is informed by two main concepts: learning as a social interaction and social reproduction. Key Words: Hellman, The Children’s Hour, Learning, classroom, social interaction